moojigizi - Shortt, Olivia (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Olivia Shortt is a Tkarón:to-based multi-disciplinary performing artist. This video contribution explores how the COVID-19 pandemic has exacerbated already existing precarities for artists and musical communities but also generated a new activism.